Impact of Online Teaching-Learning on the Student Achievement at University Level: The Current Scenario - Nimra Jamil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Online learning has been an important part in the higher educational system and has also gained prominent position recently, since the pandemic situation has occurred. Scholars and teachers considered online teaching and learning process, the reliable and effective source and medium to transfer and acquire education which has somewhat achieved the purpose of education and fulfill their aims and goals. The purpose of this research study was to highlight the impact of online teaching and learning on the students’ achievement and opportunities and the challenges which are faced by students and teachers in this era, at university level of Karachi. The chosen methodology was Quantitative, using Survey Research Method applying Random Criterion Sampling Technique. The researcher selected overall ten teachers and twenty students from each of the discipline; Bachelor, Master, M.S/M.Phil levels from East Karachi, respectively. The relevant research respondents were required to fill statements of Likert Scale via online which were analyzed by Simple Descriptive Stats, using SPSS Software. Findings revealed that online teaching-learning has somewhat both, pros and cons for the teachers as well as for students of university level. They faced similar obstacles and barriers living in remote areas, lack of resources and facilities, training, miscommunication, accessibility and financial issues etc. They also met with some opportunities such as, inclusiveness, immobility, indiscrimination and convenience. To overcome such challenges, good governance and frequent evaluation is necessary; appropriate training and enhancing skills of the teachers and resolving such issues of the students immediately, by the administration and to enhance the opportunities they get, is mandatory..